Needed- Social Survey of Steel Bands - Gomes, Albert (Sunday Guardian)
Albert Gomes comments on the steel band as a positive influence in times of serious social problems and recommends that a social survey of the steel bands be conducted.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago